KARAKTERISTIK ARSITEKTUR MASJID QUBA BAADIA DI KOTA BAUBAU - Udin, Udin; Rosmawati; Mulyadi, Yadi; Tahir Muda, Khadija (JURNAL ILMU BUDAYA, 2024)
Mosques are part of a symbol of a religious ritual as a rite of obediqwaan or a manifestation of muslims to be made a place of worship of almighty god. The diversity of mosques in the region marks that Islam is accepted as the religion believed by the people in the region. The architecture of mosques can also provide information regarding the influence of Islam comes from. The quba baadia mosque is the monumental melting point of islamic archaeology built during the reign of buton, also known during the reign of sultan muhammad idrus qaimuddin. Quba baadia mosque has been through redecorating several times, but the architectural feature is still raw. As for the problem with this research, it is knowing the characteristics that are characteristic of the differentiation from other mosques and knowing the factors that influence them.